Extracting the field theory description of a quantum many-body system from experimental data - Zache, Torsten Victor; Schweigler, Thomas; Erne, Sebastian; Schmiedmayer, Hannes-Jörg; Berges, Jürgen (Physical review. X, Expanding access, 2020)
Quantum field theory is a powerful tool to describe the relevant physics governing complex quantum many-body systems. Here, we develop a general pathway to extract the irreducible building blocks of quantum field theoretical descriptions and its parameters purely from experimental data. This determination is accomplished by extracting the one-particle irreducible (1PI) correlation functions from which one can construct all physical observables. To match the capabilities of experimental techniques, our approach employs a formulation of quantum field theory based on equal-time correlation functions only. We illustrate the theoretical foundations of our procedure by applying it to the sine-Gordon model in thermal equilibrium and then demonstrate explicitly how to extract these quantities from an experiment where we quantum simulate the sine-Gordon model by two tunnel-coupled superfluids. We extract all 1PI correlation functions up to the 1PI four-point function (interaction vertex) and their variation with momentum, encoding the “running” of the couplings. The measured 1PI correlation functions are compared to the theoretical estimates, verifying our procedure. Our work opens new ways of addressing complex many-body questions emerging in a large variety of settings from fundamental science to practical quantum technology.